Feasibility of Pulmonary Valve Balloon Dilation as Palliative Procedure in Children With Symptomatic Tetralogy of Fallot - Al-Ghanimi , Mohanad K Shukur; Munaf Jarallah,; Akram, Nabeeha Najatee (Scripta Medica, 2026)
Background/Aim: Tetralogy of Fallot (TOF) is the most prevalent cyanotic congenital heart disease, for which surgical correction remains the definitive treatment. Balloon dilatation of the pulmonary artery provides recognised immediate palliative benefits in selected TOF patients. Nonetheless, optimal patient selection and midterm outcomes remain subjects of ongoing debate. This study aimed to assess midterm results following pulmonary valvoplasty at 6 months period in children with TOF focusing on defining factors that affect response to palliative therapy.Methods: A retrospective study assessed 25 children with TOF who underwent transcatheter balloon dilatation of pulmonary valve over 5 years period. Three parameters were used to assess the palliative effect of the procedure including: oxygen saturation, pulmonary artery size and body weight, all of which measured before and 6-month post Cath. Besides, the effect of patients age, sex and presentation on palliative effects was done. Results: Of the 25 children who subjected to palliative procedure, three patients died within 24 hours. At 6 months follow-up remnant 22 children demonstrate significant improvements in oxygen saturation, pulmonary size and body weight (p < 0.001). Children older than one year had significantly higher weight and pulmonary size than infants (p = 0.002, p = 0.001), respectively. Children with spells and cerebrovascular accident (CVA) had significantly higher weight than those with spells only (p = 0.040). Conclusion: Transcatheter balloon valvuloplasty is an effective palliative intervention for children with TOF with excellent midterm outcomes for those who survived the first day. Older children and presentation with CVA indicated higher response.